Development and validation of a hydrophilic interaction liquid chromatography‐tandem mass spectrometry method for the quantification of regadenoson in human plasma and its pharmacokinetic application - Wang, Dun‐Jian; Wang, Da‐Wei; Fang, Qiu‐Chen; Shen, Ye; Zeng, Nv‐Jin; Yang, Yan‐Ling; Zhang, Hong‐Wen; Wang, Yong‐Qing; Sun, Lu‐Ning (Journal of separation science, 2022)
Regadenoson, the first selective adenosine A2A receptor agonist, is used to perform exercise stress test during radionuclide myocardial perfusion imaging. To detect the concentration of regadenoson in human plasma, a simple, fast, and sensitive tandem mass spectrometry method was established herein. Acetonitrile was used as a protein precipitation agent. Chromatographic separation was completed in 6.5 min using a BEH HILIC column (50 × 2.1 mm, 1.7 μm). The mobile phase consisted of 10 mmol/L ammonium acetate/acetonitrile (gradient elution). To quantify regadenoson and regadenoson‐d3, an API 4000 mass spectrometry in multiple reaction monitoring mode with transitions of 391.3→259.2 and 394.3→262.2, respectively, was utilized. The calibration curve was linear in the range of 0.100–50.0 μg/L, and the intrabatch and interbatch precisions were <9.7% and <13.0%, respectively, and the accuracy was 2.0–6.9%. There was no apparent matrix effect for regadenoson or regadenoson‐d3. The developed method was used to study the pharmacokinetic characteristics of regadenoson in healthy Chinese subjects.